'The Vibe is Really Important': Experiencing Hip-hop and Performance Poetry in Dar es Salaam. Issue 4 (2nd October 2021) - Adjirakor, Nikitta Dede
ABSTRACT: In the city of Dar es Salaam, hip-hop and performance poetry events are a vibrant, visible presence. Research into this phenomenon has generally explored its relation to historical, economic, social or political contexts. Such approaches are only ever rarely concerned with the experiences generated by and within the performances. This paper takes aesthetic experience as a point of departure, exploring how participants experience performance poetry and hip-hop in Dar es Salaam. Reflecting on the notion of 'vibe' as expressed by participants during fieldwork, I suggest it refers to the aesthetic experience of performance which is also a form of knowledge production through which participants engage with their everyday lives. 'Vibe' allows us to grasp the sensuous rendering of hip-hop and performance poetry and highlights the entanglement between body, space and text in producing the aesthetic experience of the performance.